ANALYSIS OF DATA PROCESSING IN MANAGEMENT INFORMATION SYSTEMS - Salbiah Salbiah; Muhammad Irwan Padli Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2024)
In the digital era, data plays a crucial role in the success of business management processes. The integration of Management Information Systems (MIS) enables organizations to efficiently collect, process, and analyze data for better decision-making. This study aims to analyze data processing in MIS, highlighting challenges, such as security issues and system integration, while also exploring solutions involving advanced technologies like Big Data and Artificial Intelligence (AI). The findings demonstrate that effective data processing significantly enhances operational efficiency and decision accuracy. Furthermore, the use of AI in MIS allows for predictive analysis, which optimizes decision-making in dynamic business environments. The study concludes that organizations must strategically implement advanced technologies to fully realize the potential of MIS and maintain competitive advantages.